2023
DOI: 10.3389/fncel.2022.1006977
|View full text |Cite
|
Sign up to set email alerts
|

The oral manifestations and related mechanisms of COVID-19 caused by SARS-CoV-2 infection

Abstract: Coronavirus disease 2019 (COVID-19) was reported to be associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, and patients present mostly with respiratory symptoms. There have been an increasing number of reports on oral manifestations, and some of these signs are informative in terms of identifying SARS-CoV-2 infection. The goal of present study was to review and synthesize the clinical characteristics and underlying mechanisms of COVID-19 oral manifestations, as well as to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 96 publications
2
3
0
Order By: Relevance
“…In this study, the common oral problems in cases infected with SARS-CoV-2 were similar to the results of Lin et al [4] The oral symptoms of "positive" infected persons are mainly concentrated in abnormal taste, gingiva red swelling or bleeding, toothache and bad breath. The development of their oral symptoms is signi cantly related to the different demographic characteristics and different living habits of the population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the common oral problems in cases infected with SARS-CoV-2 were similar to the results of Lin et al [4] The oral symptoms of "positive" infected persons are mainly concentrated in abnormal taste, gingiva red swelling or bleeding, toothache and bad breath. The development of their oral symptoms is signi cantly related to the different demographic characteristics and different living habits of the population.…”
Section: Discussionsupporting
confidence: 89%
“…The most common symptoms of oral cavity are taste disorder, dry mouth and oral mucous membrane lesions. [4] As more and more research reports on the oral symptoms of COVID-19 patients reveal oral problems after infection, for example, periodontitis. [5][6][7] Salivary gland in ammation,[8] oral candidiasis, [9] oral ulcer, [10] oral herpes, [11] oral lichen planus, [12] "novel coronavirus tongue".…”
mentioning
confidence: 99%
“…In this study, the common oral problems in cases infected with SARS-CoV-2 were similar to the results of Lin et al (4) The oral symptoms of "positive" infected persons are mainly concentrated in abnormal taste, gingiva red swelling or bleeding, toothache and bad breath. The development of their oral symptoms is significantly related to the different demographic characteristics and different living habits of the population.…”
Section: Discussionsupporting
confidence: 89%
“…This can be explained by the SARS-CoV-2 invasion of entry taste papillae cells, resulting in cellular harm and leading to the clinical symptom of dysgeusia [78]. In the mucous membrane of the tongue, immunohistochemistry studies showed ACE2 expression within the cell cytoplasm and across the cellular membrane within the non-keratinized area, alongside TMPRSS2 positioning specifically on the cellular membrane [79,80]. ACE2 was detected in minor quantities within the lamina propria of non-keratinized stratified squamous epithelia in mucosal structures.…”
Section: Tonguementioning
confidence: 99%